Genetic diversity of organoleptic properties in water yam (Dioscorea alata L.) - Egesi, Chiedozie N.; Asiedu, Robert; Egunjobi, J.K.; Bokanga, M. (Wiley, 2003)
Improving the food quality of yams (Dioscorea spp) is an ongoing challenge to yam breeders and researchers. Forty accessions of D alata were evaluated for the suitability of their tubers for the preparation of two dominant food forms (boiled and pounded) as part of an effort to identify potential parents for use in genetic improvement. Trained panellists were presented with randomised, replicated and coded samples of boiled yam tuber pieces and asked to rate them for mealiness, colour, wetness, softness and taste. The sensory attributes considered for pounded yam (dough from boiled and pounded tubers) were consistency, colour, sheen, smoothness, stickiness, elasticity and hardness. Ratings were based on hedonic scales. Cluster analysis revealed groupings of accessions into eight and nine similarity clusters for boiled yam and pounded yam respectively. The mean scores for general preference were regressed on individual attribute scores. Mealiness, colour and taste were important in the general preference for boiled yam. Consistency, colour and stickiness determined the general preference for pounded yam. Of the accessions, 67% were identified as being suitable for preparation as a boiled vegetable, while 55% were assessed to be good for pounded yam, based on the respective quality attributes evaluated.